Novel Magnetic Circuit Topology of Linear Force Motor for High Energy Utilization of Permanent Magnet: Analytical Modelling and Experiment - Bin Meng; Hao Xu; Bei Liu; Mingzhu Dai; Chenhang Zhu; Sheng Li (Actuators, 2021)
The magnetic circuit of existing linear force motors does not consider the issue of energy utilization of permanent magnets, and the structure is complicated. To achieve high energy utilization and simplify the structure, this paper presents a novel magnetic circuit topology for the linear force motors of electro-hydraulic servo-proportional valves. In order to rapidly and accurately calculate the static characteristics of the force motor, an analytical model is established by using the equivalent magnetic circuit method. The model comprehensively considers the magnetic leakage effect, edge effect, and permeability nonlinearity. A prototype of the force motor is designed and manufactured, and a special experimental platform is built. The prototype force motor has a linear force-displacement characteristic and the output force increases with the increase of the excitation currents, which can reach about 41 N at 2 A. This indicates that it is suitable as an electro-mechanical converter for electro-hydraulic servo-proportional valves. Moreover, the analytical model is used to perform parameter optimization and calculate the magnetic flux density in the working air gap and the force-displacement characteristics under different excitation currents. The results are in good agreement with the electromagnetic field finite element simulation and experimental results. They indicate that the analytical model can rapidly and accurately predict the static characteristics of the force motor. The research work provides good reference means for the design of magnetic circuit topology with consideration of the high energy utilization of permanent magnets, and also the accurate analytical modeling of valve electro-mechanical converters.